Slow Magnetic Relaxation and Spin‐Crossover Behavior in a Bicomponent Ion‐Pair Cobalt(II) Complex. Issue 33 (5th September 2017) - Shao, Dong; Deng, Lin‐Dan; Shi, Le; Wu, Dong‐Qing; Wei, Xiao‐Qin; Yang, Si‐Run; Wang, Xin‐Yi
Abstract : A bicomponent ion‐pair molecule compound [Co(Brphterpy)2 ][Co(NCS)4 ]· 2MeCN was designed and prepared for the construction of multistable functional materials. Due to the different coordination geometries of the cationic and anionic Co II ions, this compound exhibits both thermally induced spin crossover (SCO) and field‐induced single‐ion magnetism (SIM). This represents a rare example of a two‐component system with the coexistence of SIM and SCO behaviors and suggests a simple, yet very efficient strategy for the construction of multistable molecular materials. Abstract : A bicomponent ion‐pair compound with both octahedral and tetrahedral Co II centers were successfully synthesized and characterized. The octahedral Co II center undergoes a gradual and incomplete SCO, while the tetrahedral Co II center shows field‐induced single‐ion magnetic property. This simple ion‐pair strategy should be of great value for the construction of multistable molecular materials.